2016
DOI: 10.1177/0969776416681625
|View full text |Cite
|
Sign up to set email alerts
|

Migration and development at home: Bitter or sweet return? Evidence from Poland

Abstract: The existing economic literature focuses on the benefits that return migrants offer to their home country in terms of entrepreneurship and human and financial capital accumulation. However, return migration can have modest or even some detrimental effects if the migration experience was unsuccessful and/or if the migrant fails to re-integrate into the home country’s economy. In our paper, we empirically show which factors – both individual characteristics and features related to the migration experience – infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
(49 reference statements)
4
37
1
2
Order By: Relevance
“…On the basis of the migrants' educational level, it can be also concluded that our findings are in line with those reported by Jayawarna et al (2014) and Coniglio and Brzozowski (2016). Most of the investigated return migrant entrepreneurs (56%) had a general secondary education and 22% of respondents had a secondary vocational level of education, which means they were prepared for fulfilling specific but simple tasks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the basis of the migrants' educational level, it can be also concluded that our findings are in line with those reported by Jayawarna et al (2014) and Coniglio and Brzozowski (2016). Most of the investigated return migrant entrepreneurs (56%) had a general secondary education and 22% of respondents had a secondary vocational level of education, which means they were prepared for fulfilling specific but simple tasks.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to Coniglio and Brzozowski (2016), CATI (computer-assisted telephone interviewing) technique was used to collect data. As the main aim of this exploratory study was to verify a capital gains research model, the structured interview consisted of questions clustered into the following sections: (1) occupational status before migration, (2) reasons for migration, (3) occupational status in foreign country, 4reasons for returning, (4) type of business in the home country, (5) forms of capital gained abroad.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Eastern European migrants are largely perceived to be low-skilled (Parutis, 2014;Favell, 2008), as relocation implied a trade-off of lowered social status for higher income (Markova and Black, 2007;Favell, 2008). Polish migrants tend to return after economic goals have been achieved due to personal motives or attracted by welcoming economic conditions in the home country (Coniglio and Brzozowski, 2016;Fihel and Grabowska-Lusińska, 2014 for existing family members, realized goals or a desire to start a business in the home country (Sandu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Upon arrival and after the business is started, a migrant is expected to contribute to the collective budget of the household located in a home country through remittances (Taylor, 1999). Moreover, at least in the context of the initial motivations, the migration itself is perceived as a temporary event, which should help in accumulating needed capital to be invested back in the home country (Coniglio & Brzozowski, 2016). In this context, the immigrant's business development is constrained by the fact that the profits would be either continuously transferred back to the home country (to contribute to the budget of the migrant's household), or reinvested in the home country after the migration spell is resumed.…”
Section: The Role Of Migrants' Personal Strategies and Motivationsmentioning
confidence: 99%